Pengaruh Lingkungan Kerja Terhadap Kinerja Guru pada SMA Plus Pariwisata Bandung - Dewi Endah Fajariana; Luluh Abdilah Kurniawan (Asosiasi Ahli Administrasi Indonesia, 2020)
The Effect of Work Environment on Kinarja Teachers at SMA Plus Tourism Bandung. The purpose of this study was to determine the work environment at SMA Plus Tourism Bandung, to determine the performance of teachers at SMA Plus Tourism Bandung and to find out how the work environment influences the performance of teachers at SMA Plus Tourism Bandung. The sample in this study were all 32 teachers, so the technique used was the census technique. The research method used is descriptive analysis method and associative analysis. In this study using primary data, namely by making observations, and distributing questionnaires. To test the hypothesis, it is carried out using Rank Spearman correlation analysis, besides that, it is also carried out by testing the validity and reliability. The results of this study indicate that there is an influence between the work environment on the performance of teacher employees at SMA Plus Pariwisata Bandung. coefficient 41.99 and the remaining 58.01% influenced by other variables not examined by the author which can affect teacher performance achievement such as motivation, work discipline, compensation, service and so on.